2009
DOI: 10.1007/s00127-009-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Are attitudes towards mental health help-seeking associated with service use? Results from the European Study of Epidemiology of Mental Disorders

Abstract: ObjectiveTo investigate the prevailing attitudes towards mental health help-seeking in Europe, their correlates, and whether these attitudes are associated with actual service use for mental health problems.MethodData were derived from the European Study of Epidemiology of Mental Disorders, a survey representative of the adult population of six countries: Belgium, France, Germany, Italy, the Netherlands and Spain (n = 8,796). The World Mental Health Composite International Diagnostic Interview was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
138
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(166 citation statements)
references
References 48 publications
(53 reference statements)
17
138
2
9
Order By: Relevance
“…Mackenzie, Gekoski, & Knox, 2006; ten Have et al, 2010) and being Caucasian (Ward, Wiltshire, Detry, & Brown, 2013) was correlated with more favourable attitudes. Young adults were reported to have less positive attitudes towards seeking professional help than older adults (Gonzalez, Alegria, & Prihoda, 2005; Robb, Haley, Becker, Polivka, & Chwa, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Mackenzie, Gekoski, & Knox, 2006; ten Have et al, 2010) and being Caucasian (Ward, Wiltshire, Detry, & Brown, 2013) was correlated with more favourable attitudes. Young adults were reported to have less positive attitudes towards seeking professional help than older adults (Gonzalez, Alegria, & Prihoda, 2005; Robb, Haley, Becker, Polivka, & Chwa, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…A cross-temporal meta-analysis (1968–2008) showed that help-seeking attitudes changed in a disconcerting direction and became increasingly negative during the investigated period (Mackenzie et al, 2014). In a study on attitudes towards mental health service use in six European countries, ten Have et al (2010) reported that one-third of participants believed professional care for mental health problems was equitable to no help or even worse. These findings show that more effort is needed to investigate attitudes towards mental health service use, with the goal to better understand, predict, and facilitate individuals’ help-seeking for professional care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The students were also rather skeptical about the effectiveness of treatment or the chance of recovery for people with severe mental disorders. These misconceptions are rather common (Byrne, 1999;ten Have et al, 2010;Watson et al, 2005); medical and nursing students, too, were reported to hold the idea that people diagnosed with mental disorders are unlikely to recover and that they can be dangerous and violent (Aker et al, 2007;Llerena et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A estas barreras debemos añadir las relacionadas con las creencias sociales sobre la salud mental, dado que también tienen un gran impacto en la aceptabilidad de la atención integral, las preferencias y la aceptación del tratamiento (ten Have et al, 2010;Coppens et al 2013;Jorm et al, 2003). Mencionaremos a este respecto, el estigma social asociado a los trastornos mentales puesto que dificulta la búsqueda de tratamiento, lo cual junto a otras limitaciones como, el temor a que el profesional sanitario paute tratamiento farmacológico, la falta de conocimientos sobre si la sintomatología que la mujer experimenta es normal o no y el temor a que sus preocupaciones no sean tomadas en consideraciónse definen como factores determinantes a la hora de buscar ayuda (Dennis y Chung-Lee 2006;Flynn et al, 2010;Reay et al, 2011).…”
Section: Barreras Y Facilitadores Relacionados Con El Tratamientounclassified